login

Year-end appeal: Please make a donation to the OEIS Foundation to support ongoing development and maintenance of the OEIS. We are now in our 61st year, we have over 378,000 sequences, and we’ve reached 11,000 citations (which often say “discovered thanks to the OEIS”).

A281385
Triangular array T(n, k) = n^2 + n*k - k^2.
3
0, 1, 1, 4, 5, 4, 9, 11, 11, 9, 16, 19, 20, 19, 16, 25, 29, 31, 31, 29, 25, 36, 41, 44, 45, 44, 41, 36, 49, 55, 59, 61, 61, 59, 55, 49, 64, 71, 76, 79, 80, 79, 76, 71, 64, 81, 89, 95, 99, 101, 101, 99, 95, 89, 81, 100, 109, 116, 121, 124, 125, 124, 121, 116, 109, 100
OFFSET
0,4
COMMENTS
Let {y0, y1, ...} a sequence satisfying y(m) = y(m-1) + y(m-2), then y(m)^2 - y(m-1)*y(m+1) = T(y0, y1)*(-1)^m. See the Fib. Quart. link.
LINKS
Robert Israel, Table of n, a(n) for n = 0..10010 (rows 0 to 140, flattened)
F. D. Parker, The Very Existence: Problem H-248 and solution, The Fibonacci Quarterly, Vol 15, Nr 1, February 1977.
FORMULA
From Robert Israel, Jan 23 2017: (Start)
G.f. as triangle: (1 + x + y - x*y - 4*x^2*y + x*y^2 - 4*x^2*y^2 + 5*x^3*y^2)*x/((1-x*y)^3*(1-x)^3).
G.f. as sequence: (1-4*x+x^2 + (3-4*x+x^2)*Sum_{k>=0} k*x^(k*(k+1)/2) + (-1+3*x-2*x^2)*Sum_{k>=0} x^(k*(k+1)/2))/(1-x)^3.
-(5*k-1)*T(n,k-1) + (5*k-2)*T(n,k) + (5*k-3)*T(n-1,k-1) - (5*k-4)*T(n-1,k) = 0 for 1 <= k <= n-1.
(End)
EXAMPLE
Triangle begins:
0;
1, 1;
4, 5, 4;
9, 11, 11, 9;
16, 19, 20, 19, 16;
25, 29, 31, 31, 29, 25;
36, 41, 44, 45, 44, 41, 36;
...
A000032 begins {2, 1 ...} and satisfies y(m)^2-y(m-1)*y(m+1) = 5*(-1)^m.
MAPLE
seq(seq(n^2+n*k-k^2, k=0..n), n=0..10); # Robert Israel, Jan 23 2017
MATHEMATICA
Table[n^2+n*k-k^2, {n, 0, 10}, {k, 0, n}]//Flatten (* Harvey P. Dale, May 25 2024 *)
PROG
(PARI) T(n, k) = n^2 + n*k - k^2;
lista(nn) = for (n=0, nn, for (k=0, n, print1(T(n, k), ", ")); print());
CROSSREFS
KEYWORD
nonn,tabl
AUTHOR
Michel Marcus, Jan 23 2017
STATUS
approved